2019
DOI: 10.1093/heapro/daz044
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of workplace choir singing amongst Health Service staff in Ireland

Abstract: This paper explores the well-being [‘well-being’ and ‘wellbeing’ are used interchangeably in the literature. Well-being is used in this paper (except in the reference list where exact wording is maintained)] benefits of participation in a workplace choir for health service staff. A mixed method study, this project combines quantitative measures of work engagement, perceived stress, resilience levels and work absences with qualitative interviews with choir participants. It is the first study of workplace choirs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…There is a growing body of evidence that supports that the idea that singing has a variety of positive effects on both mental and physical health (Clift & Morrison, 2011; Irons, Sheffield, Ballington, & Stewart, 2020; Kreutz et al, 2003). Remarkably and specifically, several pieces of research on mental health have found a link between singing and mental well-being across different ages and settings (Clift, Manship, & Stephens, 2017; Fancourt, Finn, Warran, & Wiseman, 2019; Moss & O’Donoghue, 2019). The research conducted was varied: Some researchers analyzed the effects of singing in choirs, and others carried out research on singing groups specifically set up for research purposes.…”
mentioning
confidence: 99%
“…There is a growing body of evidence that supports that the idea that singing has a variety of positive effects on both mental and physical health (Clift & Morrison, 2011; Irons, Sheffield, Ballington, & Stewart, 2020; Kreutz et al, 2003). Remarkably and specifically, several pieces of research on mental health have found a link between singing and mental well-being across different ages and settings (Clift, Manship, & Stephens, 2017; Fancourt, Finn, Warran, & Wiseman, 2019; Moss & O’Donoghue, 2019). The research conducted was varied: Some researchers analyzed the effects of singing in choirs, and others carried out research on singing groups specifically set up for research purposes.…”
mentioning
confidence: 99%
“…The emotional, psychological and social benefits of group singing are well documented both in and outside of medical settings ( Clift and Hancox, 2001 , 2010 ; Clift et al , 2010 ; Ahessy, 2015 ; Reagon et al , 2016 ). Studies have indicated similar benefits of group singing for individuals facing socio-economic hardships and from areas of disadvantage ( Davidson, 2004 ; Bailey and Davidson, 2005 ; Cronley et al , 2018 ), as well as for adults living with a chronic mental illness or disability ( Brander et al , 2013 ; Fogg-Rogers et al , 2016 ; Moss and Donoghue, 2019 ). Research to date on choral singing indicates many physical, cognitive and social benefits ( Clift et al , 2010 ; Clift and Hancox, 2010 ; Moss et al , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research to date on choral singing indicates many physical, cognitive and social benefits ( Clift et al , 2010 ; Clift and Hancox, 2010 ; Moss et al , 2018 ). Many empirical research studies have also explored the value of singing for people with long-term health conditions, including Parkinson’s disease and stroke, respiratory illnesses, and dementia ( Skingley et al , 2017 ; Tamplin et al , 2019 ; Pentikäinen et al , 2021 ) as well as benefits for workplace well-being ( Moss and O’Donoghue, 2019 ). A systematic review by Williams et al (2018) indicates that group singing could be a promising social intervention for people with mental health conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 15 , 16 Adults with a chronic mental health condition and/or an intellectual or physical disability have experienced social, emotional, and practical gains. 17 The positive impacts of singing in a workplace choir for staff-only groups 18 , 19 and groups comprised of both staff and service users 20 have also been documented.…”
Section: Introductionmentioning
confidence: 99%